2021
DOI: 10.1002/cphc.202100204
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Reaction Equilibria in Signal Amplification by Reversible Exchange

Abstract: An in-depth theoretical analysis of key chemical equilibria in Signal Amplification by Reversible Exchange (SABRE) is provided, employing density functional theory calculations to characterize the likely reaction network. For all reactions in the network, the potential energy surface is probed to identify minimum energy pathways. Energy barriers and transition states are calculated, and harmonic transition state theory is applied to calculate exchange rates that approximate experimental values. The reaction ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Although previous studies have demonstrated the direct SABRE polarization in biocompatible solvents such as aqueous media, the resulting polarization is markedly (by an order of magnitude or more) reduced compared to that in methanol, presumably due to lower hydrogen solubility and other compounding factors. As a result, we continued with methanol as solvent for SABRE-SHEATH, and investigated the idea of performing precipitation and purification of the HP biomolecule, inspired by Eills, Knecht, and co-workers who used a related approach for fumarate. , In those studies the precipitation was achieved by adding an acid to the 13 C-hyperpolarized solutions, whereas here precipitation of pyruvate is achieved by addition of a nonpolar solvent. The present strategy may be advantageous for future clinical applications, because it avoids the use of strong acids and bases immediately before in vivo administration, which leads to additional purification and quality-assurance steps, posing translational challenges.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies have demonstrated the direct SABRE polarization in biocompatible solvents such as aqueous media, the resulting polarization is markedly (by an order of magnitude or more) reduced compared to that in methanol, presumably due to lower hydrogen solubility and other compounding factors. As a result, we continued with methanol as solvent for SABRE-SHEATH, and investigated the idea of performing precipitation and purification of the HP biomolecule, inspired by Eills, Knecht, and co-workers who used a related approach for fumarate. , In those studies the precipitation was achieved by adding an acid to the 13 C-hyperpolarized solutions, whereas here precipitation of pyruvate is achieved by addition of a nonpolar solvent. The present strategy may be advantageous for future clinical applications, because it avoids the use of strong acids and bases immediately before in vivo administration, which leads to additional purification and quality-assurance steps, posing translational challenges.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the faster exchanging substrate, anastrozole, will be expected to reach maximum hyperpolarization at lower temperatures relative to the faster exchanging substrate, letrozole. We note that the substrate exchange rate also controls the hydride exchange rate, as we have shown with ab initio calculations because hydride exchange does require substrate exchange events for monodentate ligands. These findings not only support that temperature modulation represents a key hyperpolarization parameter but also additionally suggest that relative exchange rates can be unveiled through HP temperature studies.…”
Section: Resultsmentioning
confidence: 55%
“…Considering that all evidence points to the need for substrate dissociation before hydrogen exchange, , we needed to introduce alternative possibilities for this process: partial pyruvate dissociation (Figure b) and co-ligand elimination (Figure c). To deduce which method is more probable, DFT simulations similar to the ones made for the prototypical Ir-complex with pyridine or more detailed exchange measurements are needed. The critical conclusion from this discussion for the present work is that the observed signals predominantly stem from catalyst-bound pyruvate.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 b,c illustrates possible exchange mechanisms that allow for hydrogen exchange without pyruvate exchange under the assumption that hydrogen exchange is an associative mechanism, as supported by previous work. 36 , 37 We hypothesize that the pyruvate-SABRE system enables efficient hydrogen exchange because the pyruvate binds in a bidentate fashion, which allows for hydrogen exchange via partial dissociation of pyruvate ( Figure 1 b), opening a binding site for parahydrogen without pyruvate exchange all the way into its free form. A less likely alternative is depicted in Figure 1 c, where DMSO dissociation allows for H 2 association and exchange.…”
Section: Introductionmentioning
confidence: 99%